The Neutral Detergent Fiber Digestibility of Some Tropical Grasses at Different Stage of Maturity - Mahyuddin, P; Purwantari, ND (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
The digestibility of neutral detergent fiber (IVNDFD) was determined by Telly and Terry methods in vitro on 5 tropical grasses species, Sorghum, Themeda, Iseilema, Brachyacne and Dicanthium. Stem and leaf samples were harvested at different maturity stages, started from early flowering stage to the stage when the grasses were dried. In general, IVNDFD ranged from 22% to 41%. Stages of maturity affected IVNDFD in 4 species; IVNDFD was higher in the stems than in the leaves for 2 species out of 5 species of grasses; the rest was similar. There was no correlation between NDF and IVNDFD, showing that NDF degradability in the rumen was vary. Digestibility potential of NDF (PDNDF) varied from 21% to 44% and has negative correlation with IVNDFD (r=0.75). Growth affected PDNDF in 2 species; and 3 out 5 species observed showed PDNDF in the leaves was higher than that in the stems. Negative correlation was exist between dry matter digestibility (IVDMD), water soluble extract (WSE) and protein with PDNDF.Â Grasses with stated PDNDF values have relatively high NDF retention in the rumen, which will cause low NDF or dry matter consumption. (Animal Production 11(3): 189-195 (2009)Key Words: NDF digestibility, tropical grasses, stem, leaves, maturity stage